2011
DOI: 10.1002/pca.1379
|View full text |Cite
|
Sign up to set email alerts
|

Characterisation and Quantification of Flavonoids in Iris germanica L. and Iris pallida Lam. Resinoids from Morocco

Abstract: The study shows that I. germanica and I. pallida resinoids are rich in flavonoids and that these two Iris species can be distinguished by simply analysing the polyphenol fraction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
37
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(39 citation statements)
references
References 21 publications
2
37
0
Order By: Relevance
“…[32], I. pallida Lam. [33] and I. susiana L. [59]. From the pharmacological point of view, this compound does not exert as many properties as all the other isoflavones but these are very relevant and peculiar.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…[32], I. pallida Lam. [33] and I. susiana L. [59]. From the pharmacological point of view, this compound does not exert as many properties as all the other isoflavones but these are very relevant and peculiar.…”
Section: Resultsmentioning
confidence: 99%
“…[63], I. kashmiriana Baker [64], I. pallida Lam. [33] and I. florentina L. [65]. Under the pharmacological profile, this compound is able to exert a strong anti-inflammatory action acting on prostaglandin E2 [66] and a real inhibitory effect on cytochrome P450 against the outbreak of tumor forms in different parts of the human body [17,64].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies on species belonging to the Iris genus have dealt with their biological activity [10][11][12][13], with the formation of irones and identification of their precursors [14][15][16][17][18][19][20][21][22][23][24][25], and have led to the isolation of different classes of secondary metabolites, namely triterpenoids, flavonoids and phenols [25][26][27]. In 1983, Krick [14] showed that iripallidal and iriflorental are the irone precursors ( Fig.…”
Section: Introductionmentioning
confidence: 99%
“…Iris species are rich sources of isoflavonoids. Various isoflavones like irigenin, nigricin, irilone, and irisolidone were identified in I. germanica rhizome (Ibrahim et al, 2017;Roger et al, 2012;Xie et al, 2013). In addition, benzene derivatives have been isolated from the methanolic extract of I. germanica (Asghar et al, 2010).…”
Section: Introductionmentioning
confidence: 99%